2020
DOI: 10.1038/s41598-020-60593-3
|View full text |Cite
|
Sign up to set email alerts
|

A xylan glucuronosyltransferase gene exhibits pleiotropic effects on cellular composition and leaf development in rice

Abstract: Leaf chlorophyll content is an important physiological indicator of plant growth, metabolism and nutritional status, and it is highly correlated with leaf nitrogen content and photosynthesis. in this study, we report the cloning and identification of a xylan glucuronosyltransferase gene (OsGUX1) that affects relative chlorophyll content in rice leaf. Using a set of chromosomal segment substitution lines derived from a cross of wild rice accession ACC10 and indica variety Zhenshan 97 (ZS97), we identified numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…The estimated degree of xylan glucuronidation ranged from 0.4% to 3.9% in transgenic lines, some of which are much lower than the levels observed in WT and EV controls, where approximately 4% and 3.5% of xyloses, respectively, had the GlcA branch. In another Poaceae species ( Oryza sativa ), OsGUX1 is also able to modulate the GlcA content when overexpressed or silenced (Gao et al ., 2020 ), as observed in our transgenic sugarcane lines.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The estimated degree of xylan glucuronidation ranged from 0.4% to 3.9% in transgenic lines, some of which are much lower than the levels observed in WT and EV controls, where approximately 4% and 3.5% of xyloses, respectively, had the GlcA branch. In another Poaceae species ( Oryza sativa ), OsGUX1 is also able to modulate the GlcA content when overexpressed or silenced (Gao et al ., 2020 ), as observed in our transgenic sugarcane lines.…”
Section: Discussionsupporting
confidence: 82%
“…The estimated degree of xylan glucuronidation ranged from 0.4% to 3.9% in transgenic lines, some of which are much lower than the levels observed in WT and EV controls, where approximately 4% and 3.5% of xyloses, respectively, had the GlcA branch. In another Poaceae species (Oryza sativa), OsGUX1 is also able to modulate the GlcA content when overexpressed or silenced (Gao et al, 2020), as observed in our transgenic sugarcane lines. The silencing of ScGUX2 expression and the concomitant decrease in the degree of xylan glucuronidation resulted in reduction of the plant cell wall recalcitrance, particularly seen in the increase in xylose released in the saccharification assay.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Two genes draw our attention according to their gene annotation. First is MH01t0727100-1 encoding a UDPglucuronate:xylan alpha-glucuronosyltransferase 1, which can enhance mechanical strength of the stem (Gao et al, 2020). Epigenetic plays an increasing important role for plant breeding and selection of adaptive traits.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are helpful to study rice leaf traits under drought stress. GHd2 regulates leaf senescence under drought stress by interacting with different proteins; OsHB4 overexpression can alter leaf morphology and reduce water loss; Gao et al (2020) found that OsGUX1 affects relative chlorophyll content in rice leaves [ 27 , 28 , 29 ]. At the same time, drought-tolerant rice varieties, such as Indian local varieties Kalajeera, Machakanta and Haladichudi, can also be distinguished by leaf traits [ 30 , 31 , 32 ].…”
Section: Phenology Physiological and Biochemical Indicators Of Drough...mentioning
confidence: 99%